PRESERVATION OF LOCAL VALUES BASED ON COMMUNITY PARTICIPATION IN BINUANG VILLAGE BALUSU DISTRICT, BARRU REGENCY - Hj. Sukmiah .; A. Pananrangi M (P3M Stia Al Gazali Barru and Meraja media, 2021)
[Full Paper] to pdf Copyright (c) 2021` Meraja journal